Physalis Calyx seu Fructus relieves chicken intestinal damage to heat via improving the antioxidant ability - Yin, Bin; Juan, Changning; Zhang, Rongling; Yang, Shifa; Wang, Haiting; Liu, Yueyue; Song, Shikai; Yan, Zunxiang; Yi, Yunpeng; Zhao, Zengcheng; Huang, Zhongli; Lin, Shuqian (Frontiers in Immunology, 2025)
Heat-stress-induced oxidative and inflammatory responses were important factors contributing to chicken intestinal damage. The purpose of this study was based on the antioxidant and anti-inflammatory activities of Physalis Calyx seu Fructus (Jin Deng Long, JDL) to investigate its efficacy and mechanism in relieving chicken heat stress damage. Primary chicken embryo duodenum cells and 90 30-day-old specific-pathogen-free chicken were randomly divided into control and JDL groups to establish heat stress models in vitro and in vivo. The mitigating effect was assessed through the oxidation-related enzymes and key genes, histopathology, and inflammatory factors. The results demonstrated that 100 µg/mL JDL extract could effectively alleviate heat stress damage to chicken embryo duodenum cells at 42°C. A strong antioxidant capacity of 100 µg/mL JDL extract was shown in the downregulation of LDH (at 5 h, P < 0.01) and MDA (at 5 h, P < 0.05), in the upregulation of SOD (at 5 and 10 h, P < 0.01), CAT (at 5 h, P < 0.01), and GSH-PX and T-AOC (at 0 h, P < 0.01) as well as in the high transcription level of NQO1 (at 5 and 10 h, P < 0.05) and HO-1 (at 5 and 10 h, P < 0.01). Supplements with 1 and 3 g/kg b.wt, respectively, in the drinking water both suppressed the rise of body temperature and had light pathological lesions of chicken duodenal tissues caused by heat stress at 40 ± 1°C. Accordingly, the chicken of JDL extract groups showed a lower inflammatory response as manifested by a lower level of IL-10 and higher levels of IL-6 and TNF-α and a strong antioxidant capacity characterized by lower level of MDA and higher levels of SOD and GSH-PX in the serum as well as also showed a higher transcription level of Nrf2, NQO1, and HO-1 in the duodenal tissues. In conclusion, JDL extract relieved chicken intestinal damage to heat via improving the antioxidant ability and reducing the inflammatory response.